THE EFFECT OF CREATIVITY, BUSINESS LOCATION AND HALAL LABELS ON THE INCOME OF SALE BANANA BUSINESS ACTORS IN EAST ACEH - Rahmatillah; Agustinawati; M. Subhan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to determine the effect of creativity, business location, and halal labeling on the income of banana sales business actors in East Aceh. The research sample amounted to 35 respondents of banana sale business actors. The data were analyzed using multiple linear regression and the results showed that the creativity variable (X1) had a positive and significant effect, business location (X2) and halal label (X3) had no significant effect on the income of banana sale business actors in East Aceh. So this research contributes to efforts to increase the income of banana sales business actors through strengthening creativity optimally. The implication of this research is that the higher the creativity of business actors in products, services, and innovation, the greater the potential to increase banana sales business income in East Aceh.